2015
DOI: 10.1021/acs.analchem.5b01612
|View full text |Cite
|
Sign up to set email alerts
|

Broadly Available Imaging Devices Enable High-Quality Low-Cost Photometry

Abstract: This paper demonstrates that, for applications in resource-limited environments, expensive microplate spectrophotometers-which are used in many central laboratories for parallel measurement of absorbance of samples-can be replaced by photometers based on inexpensive and ubiquitous, consumer electronic devices (e.g., scanners and cell-phone cameras). Two devices-i) a flatbed scanner operating in transmittance mode and ii) a camera-based photometer constructed from a cell phone camera, a planar light source, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 42 publications
(105 reference statements)
1
89
0
1
Order By: Relevance
“…Recentemente, Christodouleas et al 14 mostraram que um scanner de mesa pode substituir um leitor de microplacas, fazendo a quantificação de diversos corantes e leituras de placas de teste ELISA (ensaio de imunoabsorção enzimática, Enzyme-Linked Immunosorbent Assay).…”
Section: (1)unclassified
“…Recentemente, Christodouleas et al 14 mostraram que um scanner de mesa pode substituir um leitor de microplacas, fazendo a quantificação de diversos corantes e leituras de placas de teste ELISA (ensaio de imunoabsorção enzimática, Enzyme-Linked Immunosorbent Assay).…”
Section: (1)unclassified
“…A scanometry has been used as a microplate reader for high throughput screening of antioxidant based on DPPH as dry reagent on microwell plate as also used by other 28 . However, the proposed method is the first application for antioxidant sensor, measuring antioxidant capacity of GA and plant extracts.…”
Section: Resultsmentioning
confidence: 99%
“…The gray intensity, typically a result of silver enhancement is the measured signal in scanometry 27 . Scanometry was used to characterize optical feature of various dyes, such as disperse orange 3, methyl orange, fluorescein, eosin Y, rhodamine B, trypan blue, prussian blue, malachite green, methylene blue, chlorophyll b, and DPPH, in a microwell plate 28 . As the color intensity in red, green, and blue (RGB) value was mathematically converted to RGB-resolved absorbance, it was shown that flatbed scanner was comparable with spectrophotometer.…”
Section: Introductionmentioning
confidence: 99%
“…There are some smartphone based devices that are not found in the app stores, but there is a clear displacement of lab equipment using mobile technology, such as in the areas of microplate reading (Berg et al, 2015;Christodouleas et al 2015;Fu et al, 2016), live cell imaging (Walzik et al, 2015), microfluidics for cancer detection (Barbosa et al, 2015), food allergen detection (Coskun et al, 2013), and immunochromatgraphic detection of bacteria (Rajendran et al, 2014).Nonetheless, there are areas where no changes are expected; and this is the work of dangerous chemical and pathogens (e.g. Biohazard Class 3 work).…”
Section: Resultsmentioning
confidence: 99%